Strategi Pemasaran Aplikasi Spotify dalam Global - Azahra Salwa; Indri Sri Asdini; Sylvia Amanda; Aurora Elise Putriku; Lenti Susanna Saragih (Student Scientific Creativity Journal, 2024)
Spotify, present in more than 90 countries with millions of users, faces the challenge of implementing effective marketing strategies to address local market diversity while maintaining global cohesion. This strategy involves increasing product personalization to meet the diverse needs of consumers from various countries, as well as supporting the richness of local music culture in each market, including in countries with strong cultural nationalism such as Indonesia. This research aims to investigate the global marketing strategies implemented by Spotify, the world's leading music streaming platform, with a focus on product personalization, cultural adaptation, and collaboration and partnerships. The research methodology used in this research is a literature review with a qualitative approach and secondary data types. The literature review approach was chosen because it allows collecting information from various relevant sources to answer the research problem formulation. The type of data used is secondary data, obtained from sources such as Spotify annual reports, market research data, academic journal articles, and industry media. The data collection method is carried out by taking data from the library, reading, taking notes and processing research materials. The results of the study conclude that Spotify has succeeded in implementing an effective global marketing strategy to expand its reach and influence in the competitive and diverse music market. With a focus on product personalization, and collaborative partnerships, Spotify has demonstrated significant innovation in facing the challenges of globalization.